Efektivitas Pengguanaan Media Shadow Puppet - AmaAmalia Nabilah Al-Dama; Daviq Rizal (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2020)
This research aims to use shadow puppet media, which will be used to improve speaking skills in narrative text learning material. The subjects of this study were at MAK Zidny Ilma Warzuqny Fahma students. The sample in this study were students of tenth grade at MAK Ziwfa. This quantitative study focused on student's achievement in the use of shadow puppet media to increase the student's speaking skills in narrative text. The finding of this study shows that shadow puppet media significantly gives effects on student's learning. The conclusion is based on the significance value calculation of the T count > T table, so H0 is rejected; therefore, Ha is accepted. It means that there was a significant difference between student learning outcomes taught by using a shadow puppet media through English speaking skill.